Physician perspectives on de-intensifying diabetes medications. Issue 46 (November 2016) - Genere, Natalia; Sargis, Robert M.; Masi, Christopher M.; Nathan, Aviva G.; Quinn, Michael T.; Huang, Elbert S.; Laiteerapong, Neda
Abstract : Abstract: Guidelines for diabetes care recommend that physicians select individualized glycemic goals based on life expectancy, diabetes duration, comorbidity, and resources/support. When patients have stable hemoglobin A1C (HbA1C ) levels, guidelines lack recommendations on when diabetes medications should be de-intensified. To understand physicians' perspectives on de-intensifying diabetes medications in patients with type 2 diabetes. Cross-sectional survey, (February–June, 2015). Academic medical center and suburban integrated health system. Primary care and endocrinology physicians. Physicians' self-reported: awareness, agreement, and frequency of individualizing HbA1C goals; practice of de-intensifying diabetes medications; HbA1C values at which physicians de-intensify diabetes medications; and other patient factors physicians consider when de-intensifying diabetes medications. Response rate was 73% (156/213). Most physicians (78%) responded they were familiar with recommendations to individualize HbA1C goals. For patients with stable HbA1C levels, 80% of physicians reported they had initiated conversations about stopping medications; however, physicians differed in predefined HbA1C levels used to initiate conversations (HbA1C < 5.7%: 14%; HbA1C < 6.0%: 31%; HbA1C < 6.5%: 22%; individualized level: 21%). In multiple logistic regression, women physicians (odds ratio [OR] 3.0; confidence interval [CI] 1.1–8.2; P = 0.03) and physicians practicing fewer than 20 years (OR 2.8; CI 1.01–7.7; P = 0.048) were more likely to report de-intensifying diabetes medications. Individualizing glycemic goals and de-intensifying treatments are concepts well accepted by physicians in our sample. However, physicians vary considerably in reporting how they carry out recommendations to individualize and may be missing opportunities to stop or taper diabetes medications based on patients' individualized glycemic goals. Abstract : Supplemental Digital Content is available in the text